2021
DOI: 10.1016/j.reth.2021.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The promising rise of bioprinting in revolutionalizing medical science: Advances and possibilities

Abstract: Bioprinting is a relatively new yet evolving technique predominantly used in regenerative medicine and tissue engineering. 3D bioprinting techniques combine the advantages of creating Extracellular Matrix (ECM)like environments for cells and computer-aided tailoring of predetermined tissue shapes and structures. The essential application of bioprinting is for the regeneration or restoration of damaged and injured tissues by producing implantable tissues and organs. The capability of bioprinting is yet to be fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 202 publications
(215 reference statements)
0
12
0
1
Order By: Relevance
“…The various potential uses of 3D bio-printing are causing it to grow quickly into a significant industry. Numerous studies have recently found the use of 3D bio-printing in biomedical applications to be intriguing, and numerous businesses around the world have helped to further the use of this technology use in medicine by funding research projects in their labs [ 60 , 144 , 169 , 194 ]. The capacity to produce the optional product in accordance with particular patient needs makes this technology extremely advantageous for biomedical applications and devices.…”
Section: Biomedical Applications Of 3d Bio-printingmentioning
confidence: 99%
“…The various potential uses of 3D bio-printing are causing it to grow quickly into a significant industry. Numerous studies have recently found the use of 3D bio-printing in biomedical applications to be intriguing, and numerous businesses around the world have helped to further the use of this technology use in medicine by funding research projects in their labs [ 60 , 144 , 169 , 194 ]. The capacity to produce the optional product in accordance with particular patient needs makes this technology extremely advantageous for biomedical applications and devices.…”
Section: Biomedical Applications Of 3d Bio-printingmentioning
confidence: 99%
“…In situ bioprinting is a novel technology that merges with portable bioprinting, so it has some facilities to improve the disease and accelerate healing. 47 When compared to standard in vitro bioprinting, in situ bioprinting may be favored since de novo tissues are produced immediately on the predicted anatomical site in the real organism. 48 In situ bioprinting may be described as the direct printing of bioinks to build or repair living tissues or organs at a fault location in a clinical context.…”
Section: In Situ Bioprintingmentioning
confidence: 99%
“…Three-dimensional bioprinting was developed on the basis of 3D printing. Cells and scaffolds are generally made of polymers and extruded from a nozzle and cultured in 3D ( Elalouf, 2021 ; Jamee et al, 2021 ). Many organs, such as bone ( Arrigoni et al, 2017 ; Kim et al, 2021 ; Alcala-Orozco et al, 2022 ), lung ( Hu et al, 2021 ), and skin ( Gao et al, 2021c ), have already been generated by 3D bioprinting, showing plenty of potential in the future.…”
Section: Advanced Models For Ex Vivo Non Studiesmentioning
confidence: 99%